A proposal for the use of the partnership extension model to facilitate adoption of the International Institute of Tropical Agricultures plantain and banana (Musa spp.) technologies in Nigeria - Ogunlade, I.; Coulibaly, O. (International Society for Horticultural Science, 2010)
Historically, extension work within Nigeria has been largely oriented towardsa technology transfer or an advisory approach. However, neither pull nor pushextension models have yet realized the potentials of agricultural innovations,especially that of plantain and banana (Musa spp.) cultivars. Empirical data on theadoption level of these cultivars in selected states of Southern Nigeria show thatfarmers have utilized less than 50% of the potential of technologies developed by theInternational Institute of Tropical Agriculture. This paper presents Selesnew’spartnership model of extension as a measure for improving links with stakeholders.Specifically the paper reviews the process of agricultural information dissemination,identifies key actors and their roles, and draws implications for sustainablepartnering. The paper concludes that both public and private extension personnelshould be involved in initial surveys to identify different categories of plantain andbanana farmers in Nigeria, form groups based on the intensity of productionresources and provide economic and technical information to farmers